’n Interpretasie van die beeld van die brander in Jakobus 1:6 - Stander, Hennie (Verbum et ecclesia, 1994)
An interpretation of the image of the wave in James 1:6 In James 1:6 the person who doubts when he prays, is compared with a wave in the sea that is driven and blown about by the wind. It is traditionally believed that the point of the comparison is the instability of the sea waves. Thus he who doubts is like a wave which is driven hither and thither by any chance wind - like a cork floating on the wave. It is argued in this article that this interpretation does not take cognizance of the structure of the wider context. It is suggested that the point of the comparison is rather the downward movement of the wave: the crest of the high wave dives downwards and at the end the wave completely vanishes.